2002
DOI: 10.1007/s00213-002-1199-7
|View full text |Cite
|
Sign up to set email alerts
|

Potential antidepressant properties of pramipexole detected in locomotor and operant behavioral investigations in mice

Abstract: Based on other preclinical data and initial clinical results, we speculate that these effects may reflect anti-anhedonic/antidepressive properties of pramipexole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
(26 reference statements)
2
2
0
Order By: Relevance
“…Locomotion and exploratory behavior findings in the present studies are in keeping with previously published reports on pramipexole effects in other strains of mice (Lehr et al, 2002; Siuciak and Fujiwara 2004; Maj et al, 1997). 7-OH-DPAT and PD 128907, two other D3-preferential DA agonists, also reduce locomotor activity in wild-type C57BL/6J mice; this effect is not present in D3 receptor knockout mice (Pritchard et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Locomotion and exploratory behavior findings in the present studies are in keeping with previously published reports on pramipexole effects in other strains of mice (Lehr et al, 2002; Siuciak and Fujiwara 2004; Maj et al, 1997). 7-OH-DPAT and PD 128907, two other D3-preferential DA agonists, also reduce locomotor activity in wild-type C57BL/6J mice; this effect is not present in D3 receptor knockout mice (Pritchard et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Pramipexole has been found to alter nocturnal locomotion, alter operant responding (Lehr, 2002), induce hypothermia (Maj et al, 1997), and decrease the duration of immobility in the forced swim test (Kitagawa et al, 2009; Siuciak and Fujiwara, 2004). The ability to use similar PPI measures across species and the relative ease of genetic manipulations in mice makes them an attractive animal model to further study the role of D3 receptor activation in the regulation of sensorimotor gating.…”
Section: Introductionmentioning
confidence: 99%
“…A titration approach would not only minimize drug-related adverse effects but also allow to test the hypothesis that higher doses of pramipexole would increase, rather than decrease, reward responsiveness due to a preferential post-synaptic DA action. This speculation is consistent with (1) findings in rodents showing that pramipexole is effective in reversing anhedonia produced by the chronic mild stress paradigm (Willner et al 1994) and has antidepressant properties (Maj and Rogoz 1999;(Lehr 2002); and (2) clinical findings showing that higher doses of pramipexole ameliorate depressive symptoms in PD patients (Lemke et al 2006) and treatment-resistant depression (Corrigan et al 2000;Cassano et al 2004). Collectively, these preclinical and clinical findings raise the possibility that sustained pramipexole administration may alleviate depressive-particularly anhedonic-symptoms through its action on D3 receptors concentrated in the nucleus accumbens.…”
Section: Discussionsupporting
confidence: 89%
“…In line with the above observations, agonists at closely related D 2 , D 3 , and D 4 receptors, such as the antiparkinsonian agents ropinirole, pramipexole, and bromocriptine, are active in experimental models of potential antidepressant activity (Willner, 1995;Lehr, 2002). In clinical trials in Parkinson and non-Parkinson patients, D 2 /D 3 receptor agonists have also shown antidepressant properties, both alone and in synergy with selective serotonin (5-HT) reuptake inhibitors (Weddell and Weiser, 1995;Corrigan et al, 2000).…”
mentioning
confidence: 68%